Pengaruh Kualitas Pelayanan Dan Kesadaran Lingkungan Terhadap Kepuasan Masyarakat Dalam Pengelolaan Sampah Kota Palembang - Maruroh, Ina; Chairani, Annisa Larasati; Hapsari, Rindy Putri (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze the influence of service quality and public awareness on public satisfaction in waste management in Palembang City, both partially and simultaneously, while identifying the most dominant variables in influencing public satisfaction.A quantitative approach with an explanatory design was used in this study. The study population was the entire population of Palembang City, totaling 1,801,367 people, with a sample of 400 respondents randomly selected through area-based cluster sampling (city core, suburbs, and suburbs). Data were collected using a structured questionnaire with a Likert scale and analyzed using multiple linear regression supported by classical assumption tests, t-tests, F-tests, and coefficients of determination (R²) using the 2026.01.1+403 of R Studio software. The results show that service quality and public awareness, both partially and simultaneously, significantly influence public satisfaction with waste management. Service quality has a more dominant influence on public satisfaction than public awareness. These findings suggest that improving the quality of public services accompanied by strengthening public environmental awareness is a key factor in creating an effective and sustainable waste management system.